Music as an Element of Tourism Innovation: Types of Nightlife Premises in Ibiza (Spain) - Ramón-Cardona, José; Sánchez-Fernández, María Dolores; Durán-Sánchez, Amador; Álvarez-García, José (Frontiers in Psychology, 2022)
The island of Ibiza is a western Mediterranean destination known internationally for its nightlife. The aim of this paper is to make a proposal to classify the different types of premises in the Ibiza nightlife offer. This involves making a first definition that allows to delimit which businesses are parts of the sector. The methodology used is based on the case study and specifically, on the review of the promotional actions and activities carried out, completed with the visit to the premises. The classification has been made based on the offer marketed and not only on the legal forms used, as innovation goes ahead of the existing legal classifications. Although it is a particular application, due to the international importance of Ibiza, it is a good starting point to classify the nightlife offer of many other tourist destinations. The resulting typology divides the sector into two large groups: nightclubs and other premises. While nightclubs have musical parties as their main activity declared, the other premises have accommodation or catering as their main activity, with music being an element of differentiation. Nightclubs are divided into several subgroups, depending on their size and relevance. The other premises are subdivided into Beach Clubs, Hotel Clubs, Party Boats, Lounge Clubs, Disco Pubs, among others.